2009
DOI: 10.1073/pnas.0906852107
|View full text |Cite
|
Sign up to set email alerts
|

Metal templated design of protein interfaces

Abstract: Metal coordination is a key structural and functional component of a large fraction of proteins. Given this dual role we considered the possibility that metal coordination may have played a templating role in the early evolution of protein folds and complexes. We describe here a rational design approach, Metal Templated Interface Redesign (MeTIR), that mimics the time course of a hypothetical evolutionary pathway for the formation of stable protein assemblies through an initial metal coordination event. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
156
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 34 publications
4
156
0
3
Order By: Relevance
“…Such coordination geometries are commonly found in proteins 33,54 and have been engineered previously. [37][38][39][40][41][42] On the basis of the crystal structures of T4L and MBP in each protein, we chose three pairs of solvent-accessible residues that are located close to the ends of helices (Fig. 1).…”
Section: Rationale and Design Of Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such coordination geometries are commonly found in proteins 33,54 and have been engineered previously. [37][38][39][40][41][42] On the basis of the crystal structures of T4L and MBP in each protein, we chose three pairs of solvent-accessible residues that are located close to the ends of helices (Fig. 1).…”
Section: Rationale and Design Of Mutationsmentioning
confidence: 99%
“…37 The crystal structure of this complex reveals a trimer of Atx1 molecules mediated through the bound tetrathiomolybdate molecule. Tezcan and coworkers [38][39][40][41][42] have studied metaldirected protein self-assembly on the model protein, cytochrome b 562 , focusing primarily on the evolution of metal coordination in protein folds and complexes. Their work has shown that by introducing histidine mutations on the alpha helical surface of cytochrome b 562 , the protein can oligomerize to form dimers to tetramers, all of which are mediated through metal binding.…”
Section: Introductionmentioning
confidence: 99%
“…Protein-folding malfunctions play key roles in numbers of disorders and the metal coordination is a key structural and functional factor in most proteins [12]. It is more probable that various stresses, for example, can produce defective structure formations of proteins that perturb homeostasis of transition metals (mainly Cu + or Fe…”
Section: Camentioning
confidence: 99%
“…Despite these successes, few studies have addressed the issue of how two proteins with few interfacial interactions are able to find each other by overcoming the entropic barriers in early events of protein structural evolution. In this issue, Salgado et al (1) propose and demonstrate that metal ions could possibly fulfill such a role by being a matchmaker. In a strategy called metal templated interface redesign (MeTIR), these investigators first designed histidines into the interface of cytochrome cb 562 , a monomeric protein even at millimolar concentration, to allow Zn 2+ -histidine coordination to bring monomeric cytochrome cb 562 together.…”
mentioning
confidence: 99%
“…Matchmakers bring together two people who otherwise have little chance of being associated with each other, nurture the closeness between the two parties by enhancing their commonality and smoothing out their differences, and then quietly disappear after the marriage. In this issue, Salgado et al (1) describe such a matchmaker for single-domain proteins, with significant implications for protein structural evolution and design ( Fig. 1).…”
mentioning
confidence: 99%